Pengaruh Testimoni dan Diskon terhadap Ketertarikan Belanja di Shopee pada Santri Putri Pesantren At-Tahdzib Jombang - Ashar, Asyarurahim; Amalia, Laili Rizqi; Septian, Aris Dwi (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2025)
Discounts are proven to be able to provide more affordable price incentives for consumers, thus creating a strong sense of urgency to make a purchase. Although testimonials also have a significant influence, the role of discounts is more prominent in shaping consumer perceptions, beliefs, and purchasing decisions. This finding indicates that female students tend to consider price factors and special offers when making purchases on e-commerce platforms. This research aims to analyze the influence of discounts and testimonials on consumer purchase interest in the Shopee e-commerce platform among female students at the At-Tahdzib Islamic Boarding School in Jombang. Using a quantitative approach and regression analysis, the results show that discounts have a more dominant influence compared to testimonials in affecting consumer purchase interest. Research approach refers to the strategy or method used to collect data, analyze information, and achieve research objectives. In this study, the researcher used a quantitative approach. The quantitative approach uses numerical measurements and statistical analysis to test hypotheses and explain relationships between variables. The implication of this research is that sellers on the Shopee e-commerce platform can design marketing strategies that focus on discounts and attractive price offers, while still paying attention to the role of testimonials in building consumer trust.